2019
DOI: 10.15406/ogij.2019.10.00423
|View full text |Cite
|
Sign up to set email alerts
|

Rare cervical malignancy: a case of small cell neuroendocrine tumour of the cervix

Abstract: Objective: To describe a case of a small cell neuroendocrine tumour of the cervix. Case report: a 46 year old lady was diagnosed with an infiltrative high grade small cell neuroendocrine adenocarcinoma which was infiltrating the uterus, after she presented with unprovoked vaginal bleeding. Surgery was done successfully, after which she was referred for chemotherapy. Discussion: MR imaging was essential in staging the tumour. It is also important to appreciate the rarity of such a diagnosis and the intricacies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…In rare cases, patients can have hypercalcemia, Cushing's syndrome, and syndrome of inappropriate ADH secretion if endocrinologically active [ 6 ]. In a case reported by Dalli et al [ 7 ] and in two cases out of three reported by Giordano et al [ 4 ], the presentation was post-menopausal unproved vaginal bleeding, which is similar to our case.…”
Section: Discussionsupporting
confidence: 89%
“…In rare cases, patients can have hypercalcemia, Cushing's syndrome, and syndrome of inappropriate ADH secretion if endocrinologically active [ 6 ]. In a case reported by Dalli et al [ 7 ] and in two cases out of three reported by Giordano et al [ 4 ], the presentation was post-menopausal unproved vaginal bleeding, which is similar to our case.…”
Section: Discussionsupporting
confidence: 89%